Morphological, Molecular Identification and Virulence of Entomopathogenic Fungi Isolated From Dendroctonus micans (Kugelann,1794) (Coleoptera: Curculionidae) - Sevda İşık; Ali Soydinç; Seda Biryol (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2024)
In this study, to determine an effective fungal agent against Dendroctonus micans (Kugelann, 1794) (Coleoptera: Curculionidae), which causes significant economic losses in forested areas, Picea orientalis (L.) Link in Artvin between 2021-2022. Dendroctonus micans larvae and adults were collected from the trees, and 18 fungi were isolated from larvae and adult insects. Morphological (infection type, colony morphology, spore form) and molecular (ITS1-5.8S ITS2 gene region) characterization determined that the isolates were Metarhizium anisopliae (Metschn.) Sorokin, 1883 (Hypocreales: Clavicipitaceae), M. robertsii, M. pinghaense and Clonostachys rosea Samuels & Rossman, 1999 (Hypocreales: Bionectriaceae). Isolates M. robertsii (OZM4) and M. pinhaense (OZM9) have been isolated from this pest for the first time. As a result of insecticidal activity tests performed on D. micans larvae and adults of 1x107spore/ml spore suspension, the larvae, M. anisopliae (OZM2), showed a mortality rate of 92% within 7 days and adults mortality was determined 100% at the end of the experiment, and mycosis rates were found to be consistent with mortality rates. These results show that isolates with high virulence are promising in microbial and integrated control applications against important forest pests.